Intersubjective Consistency of Knowledge and Belief - Giacomo Bonanno (University of California, Department of Economics, 1998)
We consider interactive epistemic models where individuals are described by both their ""knowledge"" and their ""beliefs."" Three intersubjective consistency conditions are examined: Intersubjective Caution (if an individual believes something to be common belief then he knows it to be common belief), Truth of Common Belief (only true facts are commonly believed) and Qualitative Agreement. These conditions are employed in characterizations of the following properties which describe either the extent of intersubjective truth and/or the logic of common belief: common belief in no error, common knowledge of common belief, negative introspection of common belief, coincidence of common knowledge and common belief, and collapse of individual belief and knowledge. We also discuss to what extent the three fundamental conditions can be viewed as intersubjective rationality conditions.
Keywords: 330